Environmental and genetic factors affecting milk production of Butana cattle in the Sudan - Alim, K.A. (American Dairy Science Association, 1962)
Factors affecting milk production in the Butana are investigated. Production records of 353 Butana cows with 1,311 calvings during the years 1943-57 from a governmental dairy farm herd on the north of Atbara, Sudan were analysed. Heifers averaged 44 months old at first calving. The average interval between consecutive calving was 416 days. The average milk yield in 253 days was 3,129 lb, with a standard deviation of 1,709 lb. There were highly significant differences between all production traits at different years. No real differences were evident in milk yield records due to month of calving or age of cows in lactation. Repeatability estimates of single record milk yield, calving intervals, lactation periods, and dry periods were: 0.415± 0.037, 0.111±0.039, 0.415 ± 0.043, and 0.221±0.037, respectively. Heritability of a single record milk yield was estimated as 0.278± 0.232 and two records as 0.302±0.286. The total generation length was 25.87 years, and it was estimated that the annual genetic improvement in milk yield amounted to about 0.7% of the herd average. Most of the improvement had been brought about by the selection of the sires used.